PERAN SESEPUH ADAT DAN MEDIA KOMUNITAS MASYARAKAT KASEPUHAN CIPTAGELAR DALAM MENJAGA IDENTITAS KEBUDAYAAN ASLI - Dalil, Firas; Rahardjo, Turnomo (Interaksi Online, 2019)
This study aims to explain how Kasepuhan Ciptagelar in Sukabumi, through customary elders and community media maintains the existence of customs that become their identity while spreading it to the outside community. Kasepuhan Ciptagelar is classified as a Co-culture group (Mark Orbe) among the dominant cultures. The Identity Negotiation Theory (Stella Ting-toomey) is used to explain how the community in the adat system interacts with the dominant cultural community and the Theory of Cultural Studies (Stuart Hall) is used to examine the use of community media to disseminate customary values to the wider community. This type of research is qualitative descriptive with a phenomenological approach. The informants of this study were indigenous elders and Kasepuhan Ciptagelar community media workers. The results of the study show that the values and systems of customary norms are identities which reflected by indigenous peoples wherever they are. Customary elders and the community applied the concept of MIA (mindfull identity attunement) through welcoming, mentoring and rewarding each migrant without limiting the curiosity of the immigrant community. Mindfullnes in interacting and communication competence of indigenous people increases along with the number of visitors who come. Regardless of how stereotypes are given from dominant cultural communities, indigenous people have pride in their cultural identity. Submission of cultural identity also occurs through community media managed by Kasepuhan Ciptagelar. Through community media, Kasepuhan Ciptagelar creates rival hegemony in order to minimize the influence of agreed dominant culture potentially damaging customary values